Makna Nilai Dan Fungsi Sosial Ritual Adat Loka Po’o (Analisis Makna Simbolik Ritual Adat Loka Po’o Di Desa Koro Bhera, Kecamatan Mego, Kabupaten Sikka, Provinsi Nusa Tenggara Timur) - Gobang, Yonas; Noang, Edmondus Iswenyo; Ndopo, Ronaldus; Nabung, Adrianus (Universitas 17 Agustus 1945 Surabaya, 2022)
Loka Po'o is a traditional ritual of the Lio’s which held at the beginning of every planting season. This ritual is believed to be a bridge to convey requests for the fertility of plantation land, rice fields. The Loka Po’o ritual is also a thanksgiving ritual to Du'a Lulu Wula Ngga'e wena land (God Ruler of the Universe) for the harvest obtained in the previous planting season. The ritual is a proof of the rich tradition of the people of Koro Bhera Village needs to be preserved by the younger generation. The researcher examines this ritual from the perspective of communication science, especially the analysis of symbolic and social values. The result, Loka Po'o ritual contains a wealth of positive values in social life, namely: mutual cooperation, mutual assistance, and religious values.